TRACE FOSSILS AND EXTENDED ORGANISMS: A PHYSIOLOGICAL PERSPECTIVE - Turner J.S. (My University, 2003)
Organism-built structures have long been useful artifacts for students of evolution and systematics, because they represent a permanent record of a set of behaviors. These structures also represent an investment of energy by an organism, and to persist in the fossil record, the energetic investment in the structure must pay off for the organisms that build it, in either improved survivorship, increased physiological efficiency or enhanced fecundity. A useful way to think about this aspect of organism-built structures is to treat them as external organs of physiology, channeling or tapping into energy sources for doing physiological work. This paper reviews briefly how burrows and nests can act as external organs of physiology at various levels of organization, and introduces the notion of organism-built structures as adaptive structures, in which feedback controls confer adaptability to organisms' external constructions, and which promote homeostasis of the organism and its local environment. Miller's concept of trace fossils as behavioral tokens reflects this aspect of animal-built structures, and may illuminate many unanswered questions concerning their origins and persistence in the fossil record.
Keywords: BIOGENIC STRUCTURES; EXTENDED PHYSIOLOGY; EXTENDED ORGANISM; BOUNDARY LAYER; INDUCED FLOW; NATURAL CONVECTION; KELP; TERMITE; FLUID MECHANICS; SOIL WATER